Mobile technology usage: the shift of focus to cultivate high level thinking skills (HOTS) in the Malay language education system - Mohamed Mokhtar, Marzni; Jamil, Marni (Horizon Research Publishing, 2020)
The rapid growth of information and communication technology has also affected the current education world. Teachers as individuals in charge of teaching and guiding pupils in the classroom need to undertake a paradigm shift related to pedagogy conducted. Teachers should be wise in balancing between the content of knowledge and information to be conveyed and then combine it with other skills, especially the skill of high order thinking (HOTs) by using mobile technology. The use of mobile technology is now increasingly gaining attention in the world community in all matters. Hence, the educational system is able to offer chances and opportunities to embrace high-level thinking by making mobile technology a device that brings about and facilitates teachers to deliver knowledge and skills to pupils of generation Z.